2018
DOI: 10.1186/s12245-018-0169-8
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic utility of D-dimer and other clinical variables in pregnant and post-partum patients with suspected acute pulmonary embolism

Abstract: BackgroundPulmonary embolism (PE) during pregnancy remains one of the leading causes of maternal morbidity and mortality in the developed world. However, there is a paucity of high-quality evidence resulting in a lack of consensus in managing this group of patients. The aims of the study were to address the diagnostic utility of D-dimer for suspected PE in pregnant and post-partum patients and to identify any clinical presentation variables that are predictors of PE in this group of patients.MethodsA retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Complete blood count with differential, kidney function with electrolytes including calcium and magnesium levels, liver function tests (lactate dehydrogenase) and coagulation tests (INR, PTT, fibrinogen), C-reactive protein and procalcitonin, NT-proBNP, troponin should be done at admission [84]. D-dimers are generally elevated in pregnancy and thus not reliable [85]. Lymphopenia is common in COVID-19, but when presenting with increased neutrophil count, bacterial sur-infection is likely and should be treated accordingly.…”
Section: Initial Assessmentmentioning
confidence: 99%
“…Complete blood count with differential, kidney function with electrolytes including calcium and magnesium levels, liver function tests (lactate dehydrogenase) and coagulation tests (INR, PTT, fibrinogen), C-reactive protein and procalcitonin, NT-proBNP, troponin should be done at admission [84]. D-dimers are generally elevated in pregnancy and thus not reliable [85]. Lymphopenia is common in COVID-19, but when presenting with increased neutrophil count, bacterial sur-infection is likely and should be treated accordingly.…”
Section: Initial Assessmentmentioning
confidence: 99%
“…4,5 Clinicians pay specific attention to patients with a positive D-dimer test because it has a sensitivity of approximately 97% for PE. However, the specificity of a positive D-dimer test for PE is only approximately 40%, 6,7 causing difficulty for clinicians, especially clinicians inexperienced with PE diagnosis, in determining the probability of PE and whether the gold standard CTPA test is needed for an accurate diagnosis. In addition, it is not feasible to extensively use CTPA to reduce the risk of a missed diagnosis in PE.…”
Section: Introductionmentioning
confidence: 99%
“…D-dimer is a minor protein product, which is found in circulation in negligible amounts because of endogenous fibrinolysis. [ 11 ] Many studies have examined the level of D-dimer during pregnancy[ 10 11 12 ] and showed that D-dimer values were higher during pregnancy compared to nonpregnancy. In addition, increased levels of D-dimer were observed in the third trimester of normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased levels of D-dimer were observed in the third trimester of normal pregnancy. [ 10 ] However, the reason for the increase in the amount of D-dimer during pregnancy may be continuous coagulation, and fibrinolysis increases the production of intrinsic and extrinsic coagulation factors during normal placental growth. [ 13 14 ] This results in a physiological increase in the concentration of D-dimer in the blood of the mother during pregnancy until delivery, which is not necessarily associated with thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation